2001
DOI: 10.1108/eum0000000006212
|View full text |Cite
|
Sign up to set email alerts
|

Combined mixed convection and radiation in ventilated cavities

Abstract: The interaction between mixed convection and thermal radiation in ventilated cavities with gray surfaces has been studied numerically using the Navier‐Stokes equations with the Boussinesq approximation. The effect of thermal radiation on streamlines and isotherms is shown for different values of the governing parameters namely, the Rayleigh number (103 ≤ Ra ≤ 106), the Reynolds number (50 ≤ Re ≤ 5000) and the surfaces emissivity (0 ≤ ε≤ 1). The geometrical parameters are the aspect ratio of the cavity A = L’/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Later, Raji and Hasnaoui [11] investigated the mixed convection in ventilated cavities where the horizontal top wall and the vertical left wall were prescribed with equal heat fluxes. Similar investigations were also carried out by the same authors taking into consideration the effect of the thermal radiation on mixed convection [12].…”
Section: Introductionmentioning
confidence: 52%
“…Later, Raji and Hasnaoui [11] investigated the mixed convection in ventilated cavities where the horizontal top wall and the vertical left wall were prescribed with equal heat fluxes. Similar investigations were also carried out by the same authors taking into consideration the effect of the thermal radiation on mixed convection [12].…”
Section: Introductionmentioning
confidence: 52%
“…Another configurations and heat flux conditions in ventilated cavities were analyzed by Raji and Hasnaoui [6][7][8][9]. On recent works Raji that radiation contributes to the homogenization over temperature distribution and a decrease on the maximum temperature inside the cavity can be observed [9]. Singh and Sharif [10] carried out a study with 6 different configurations of inlet and outlet of air.…”
Section: Introductionmentioning
confidence: 98%
“…The authors reported in [3] and [4] that flow patterns describe oscillating patterns due to floating forces generated by the heat source, and cooling efficiency improves if the air outlet is located on the lower side of the vertical wall; later in [5], the authors extended the study to an inclined channel, and they concluded that the best behavior on heat transfer is found on vertical channels. Another configurations and heat flux conditions in ventilated cavities were analyzed by Raji and Hasnaoui [6][7][8][9]. On recent works Raji that radiation contributes to the homogenization over temperature distribution and a decrease on the maximum temperature inside the cavity can be observed [9].…”
Section: Introductionmentioning
confidence: 98%
“…Among of these systems, Raji and Hasnaoui [2] studied numerically the interaction between laminar mixed convection and thermal radiation in ventilated cavities with gray surfaces. Their results showed that thermal radiation significantly alters the temperature distribution, the flow fields and the heat transfer across the active walls of the cavities.…”
Section: Introductionmentioning
confidence: 99%